The Entrepreneurial Ecosystem in Egypt: A Gendered Perspective - Khayal, Hanan (AUC Knowledge Fountain, 2021)
This study aims to investigate the Egyptian entrepreneurial ecosystem from a gendered perspective, focusing on women entrepreneurs and experts’ views of the ecosystem and its effect on women entrepreneurs and their ventures. The study uses a qualitative approach incorporating semi-structured interviews with fourteen women entrepreneurs and experts with long experience in the field of entrepreneurship. The analysis shows that the pillars of the ecosystem namely policy, culture, finance, education and training, and networking have impactful influences on women entrepreneurs in Egypt, affecting their entrepreneurial journey across the different levels of venturing. Women entrepreneurs are at a disadvantage within the ecosystem due to the high prevalence of gendered stereotypes and prejudices surrounding them, lack of coordination among the players within the ecosystem, scarcity of information on available resources, and lack of understanding of the significance of women entrepreneurship and its benefits to the economic and social conditions of the country at large. The study highlights the paradox between an increasing number of available resources and services to entrepreneurs and the low number of women-owned businesses established and enhanced after receiving these services. Findings showed that these services lack quality and depth, and are not accommodating to women entrepreneurs’ needs. Ultimately, the study concluded that women need more support within the ecosystem, where they are provided with the same range of opportunities and benefits, and allowed a fair business journey on par with their male counterparts. The study contributes to the available literature on women entrepreneurship and the entrepreneurship ecosystem alike, where it highlighted the main challenges and shortcomings of the ecosystem’s pillars. It explains how it impacted women entrepreneurs’ journeys and ventures and allows for recommendations that would create a healthier and more inclusive ecosystem for women entrepreneurs.